Efektivitas Pelaksanaan Program Pembiasaan Sholat Berjamaah Dalam Membentuk Karakter Disiplin Siswa di SMA Aisyiyah 1 Palembang - Adelia Rizki Eka Putri; Candra Darmawan; Anang Walian (ScidacPlus, 2023)
This study aims to evaluate the effectiveness of implementing the congregational prayer habituation program in shaping the disciplinary character of students at SMA Aisyiyah 1 Palembang. The implementation of this congregational prayer habituation program has been running at Aisyiyah 1 Palembang High School. This study uses quantitative research methods with a descriptive approach. Data was collected through questionnaires, observations, and documentation related to the implementation of the congregational prayer habituation program at SMA Aisyiyah 1 Palembang. The research respondents consisted of students of class X and XI. The sample in this study were 51 students. The variables of this study consist of program implementation (X) and disciplinary character (Y). Data processing was assisted by the SPSS for Windows version 25 program. The results of this study based on the results of the normality test showed that the significance of 0.200 was greater than the specified value of 5%. The result is 0.200 > 0.05, it can be concluded that Ha is accepted and the residual data is normally distributed. The results of linear regression based on data analysis showed that the value of tcount = 3.597 while the significance value was 0.001. Then the significance value is smaller than the value of 0.05 or 0.001 <0.05 meaning that there is a significant influence between the program implementation variable (X) and the disciplinary character variable (Y). supporting and inhibiting factors in the implementation of the congregational prayer habituation program in shaping the character of student discipline. There are several supporting factors that can help in creating a disciplinary character in the implementation of prayers, namely the family environment, school environment, teachers, surrounding environment, and good association. All of these factors have a very important role in shaping the character of discipline in prayer so that children can grow into individuals who have strong disciplinary character in praying. The inhibiting factor is the lack of parental supervision and association with friends. With these efforts, it is hoped that it can reduce the inhibiting factors for the implementation of prayers at SMA Aisyiyah 1 Palembang, so that the character of discipline in worship can be created for students studying at the school.